Identification of proteomic changes for dexamethasone-induced ocular hypertension using a tandem mass tag (TMT) approach. (March 2022) - Liang, Xin; Li, Ning; Rong, Yan; Wang, Junming; Zhang, Hong
Abstract: Glaucoma, characterized by ocular hypertension, is the second most common cause of vision loss worldwide. The potential mechanism, however, has yet to be elucidated. This study aimed to assess the proteomic changes in the trabecular meshwork (TM) in an observational animal model of Dexamethasone (DEX)-induced OHT. OHT was induced in Wistar rats by applying DEX topically to both eyes for 28 days. Intraocular pressure (IOP) was evaluated and TM protein expressions and protein identification were performed by a TMT-based method for comparing the changes in proteins between DEX-induced OHT and the control group. The results showed that average IOP was elevated significantly in rats of the DEX-induced OHT group compared to controls. Further, a total of 4, 804 proteins in the control and DEX-induced OHT group were determined and 4, 064 proteins were quantified via TMT proteomics. In total, 292 significantly abundant proteins (173 downregulated and 119 upregulated) were identified between the two groups. Proteins associated with vision, including Crystallin related proteins, filensin, rhodopsin, recoverin, phosducin were lowered in the DEX-induced OHT group relative to the control group. In summary, DEX induced extensive changes in the protein expression of TM tissue. These proteins were found to be candidate biomarkers for personalized treatment and diagnostic research in the future for improving visual health. Highlights: A TMT-based proteomics approach was used to investigate the changes of proteins in TM tissue in DEX-induced ocular hypertension rats compared to control. Our study provides an in-depth analysis of trabecular meshwork proteomic makers in DEX-induced ocular hypertension rats. Significantly abundant proteins were further characterized using bioinformatics tools. Proteins, mainly including Crystallin related proteins, filensin, rhodopsin, recoverin, phosducin lowered in DEX-induced ocular hypertension were potential proteomic markers for disease diagnosis and treatment.